Waterborne polyurethane adhesive, preparation method and application thereof in lithium ion battery

By preparing an optimized aqueous polyurethane binder, the problems of insufficient dispersion of the negative conductor conductive agent and electrolyte resistance of lithium-ion batteries are solved, and the cycle life and safety performance of the battery are significantly improved.

CN119752394APending Publication Date: 2025-04-04WANHUA CHEM GRP BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510005733.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The prior art has shortcomings in improving the dispersion of the negative electrode conductive agent of lithium-ion batteries and the resistance of electrolytes, resulting in poor cycle life and safety performance of the battery.

Method used

The aqueous polyurethane binder prepared by polymerization reaction from polyisocyanates, polyols, hydrophilic compounds and small molecule additives is used to optimize its mass ratio and composition to improve the dispersion of the conductive agent and the electrolyte tolerance.

Benefits of technology

The uniform dispersion of conductive agent in the electrode is achieved, the long-term electrochemical performance and safety performance of the battery are improved, and the strength and flexibility of the adhesive are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005226805470000081
    Figure BDA0005226805470000081
  • Figure BDA0005226805470000082
    Figure BDA0005226805470000082
  • Figure BDA0005226805470000083
    Figure BDA0005226805470000083
Patent Text Reader

Abstract

The invention relates to an aqueous polyurethane adhesive, a preparation method and application thereof in a lithium ion battery. The aqueous polyurethane adhesive for the battery is prepared by polymerization reaction of raw materials including polyisocyanate, polyol, hydrophilic compound, small molecule auxiliary agent and the like. The aqueous polyurethane adhesive has excellent dispersibility for carbon-based materials such as graphite, silicon carbon, conductive carbon black, carbon nanotubes and the like, has excellent resistance to electrolyte and its own adhesive film has high strength and flexibility, an electrode coating liquid composition containing the aqueous polyurethane material and an electrode for a storage device containing the solid component in an electrode layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries, and more specifically, relates to a waterborne polyurethane adhesive, a preparation method and application thereof in lithium ion batteries. Background Art

[0002] In recent years, with the rapid development of electrochemical energy storage, the demand for high energy density and high rate performance storage devices such as 3C digital, electric vehicles, electric aircraft, and electric ships has been increasing. This demand is highly anticipated for storage devices with high energy density, such as lithium-ion secondary batteries, lithium-ion capacitors, and all-solid-state batteries.

[0003] The negative electrode of such a storage device is usually made of thicker graphite electrodes or silicon-carbon electrodes with higher energy density. However, with the increase in electrode thickness or the addition of low-conductivity active materials such as nano-silicon, the electronic conductivity of the electrode needs to be improved. Therefore, the type of conductive agent gradually changes from traditional conductive carbon black to multi-walled carbon nanotubes or single-walled carbon nanotubes. However, the high conductivity advantage of carbon nanotubes also has the characteristics of higher specific surface area and fewer surface defect groups. The existing conductive agent dispersant is mainly CMC (sodium carboxymethyl cellulose), which can meet the requirements for the dispersion of graphite and a small amount of conductive carbon black, but for electrode slurries with carbon nanotubes or higher conductive agent content, using only CMC often leads to excessive slurry viscosity or difficulty in slurry filtration (poor dispersibility), especially in the silicon-carbon negative electrode slurry system. After drying, the coated electrode can be found to be entangled and agglomerated by SEM (scanning electron microscope). The uniformity of the distribution of the conductive agent in the electrode has a great influence on the cycle life and cycle expansion in the long-term electrochemical performance of lithium-ion batteries. Therefore, improving the uniform dispersion of the high-efficiency conductive agent in the aqueous negative electrode coating liquid composition is an issue that needs to be urgently addressed in the industry.

[0004] At present, most patents mainly optimize the dispersant in the single-walled carbon nanotube slurry to improve the distribution of the conductive agent in the final actual negative electrode coating solution, but the actual effect is very limited. For example, the small molecular weight dispersant provided in the CN106413949B patent is very easy to dissolve in the electrolyte in the full battery cell, causing side reactions during the charging and discharging process of the battery cell.

[0005] The silicon-carbon negative electrode binder PAA (polyacrylic acid copolymer) currently used in the industry has good tolerance to electrolytes and excellent adhesion, but it has two defects: poor dispersion of the conductive agent, and a hard and brittle film after the adhesive dries, which causes the lithium-ion battery's cycle capacity to drop easily in the later stages.

[0006] Waterborne polyurethane as a negative electrode binder has not been commercially used so far. Its main drawback is its weak bonding strength. Although the patent CN

[0007] The aqueous polyurethane dispersion in 117777406A and the aqueous polyurethane dispersion composition in patent CN 113711383 A have good comprehensive resistance to electrolyte and other solvents, and have certain dispersibility for conductive agents. However, in actual applications, the electrode demolding and material falling off often occur due to weak adhesion, resulting in poor final long-term electrochemical performance and safety performance.

[0008] Therefore, it is urgent for the industry to invent an adhesive that can efficiently disperse the conductive agent, has good tolerance to the electrolyte, has both strength and flexibility in the adhesive itself, and has excellent long-term electrochemical performance and safety in the battery cell. Summary of the invention

[0009] In order to solve the defects and problems existing in the above-mentioned prior art, the present invention provides an aqueous polyurethane binder with excellent dispersibility for conductive agents and excellent long-term electrochemical performance of battery cells and a preparation method thereof, an electrode coating liquid composition containing the aqueous polyurethane material, an electrode for a storage device containing the solid component in an electrode composite layer, and a storage device having the electrode for a storage device.

[0010] In order to achieve the purpose, the present invention adopts the following technical solutions:

[0011] On the one hand, the present invention provides a water-based polyurethane binder for batteries, which is prepared by polymerization reaction of raw materials including polyisocyanate, polyol, hydrophilic compound, small molecule additive and the like.

[0012] In the present invention, in parts by weight, the mass ratio of the polyisocyanate, polyol, hydrophilic compound and small molecule auxiliary agent is 15-50: 40-75: 2-10: 0.05-5, and the preferred mass ratio is 20-40: 50-70: 3-8: 0.1-4.

[0013] In the present invention, the polyisocyanate is not particularly limited, and polyisocyanates commonly used in the art can be used. Specifically, aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, aromatic aliphatic polyisocyanates can be listed. As aliphatic polyisocyanates, tetramethylene diisocyanate, dodecamethylene diisocyanate, hexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, etc. can be listed. As alicyclic polyisocyanates, isophorone diisocyanate, hydrogenated xylylene diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 1,4-cyclohexane diisocyanate, methylcyclohexylene diisocyanate and 1,3-bis(methyl isocyanate)cyclohexane can be listed. As aromatic polyisocyanates, toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, etc. can be cited. As aromatic aliphatic polyisocyanates, dialkyl diphenylmethane diisocyanate, tetraalkyl diphenylmethane diisocyanate, etc. can be cited. In addition, dimers or trimers of these organic polyisocyanates, modified products such as biuret isocyanates can be cited. It should be noted that these can be used alone or in combination of two or more.

[0014] Among the above-mentioned polyisocyanates, alicyclic and / or aromatic isocyanates are preferred from the viewpoint of dispersibility and electrolyte resistance, and specifically, 4,4′-dicyclohexylmethane diisocyanate, isophorone diisocyanate, 1,3-bis(isocyanatomethyl)cyclohexane, and hexamethylene diisocyanate are preferred.

[0015] In the present invention, the polyol is an olefin polyol containing 1.5 or more active hydrogens. Specifically, polyols such as polybutadiene polyol, polyisoprene polyol, polychloroprene polyol or their hydrogenated polyols, and polyols obtained by copolymerizing olefin compounds such as styrene, ethylene, vinyl acetate, acrylate, etc. in polybutadiene polyol or their hydrogenated polyols can be listed. Polybutadiene polyol, polyisoprene polyol, hydrogenated polybutadiene polyol, and hydrogenated polyisoprene polyol are particularly preferred. It should be noted that they can be used alone or in combination of two or more.

[0016] The molecular weight of the polyol is preferably 500-4000 in terms of number average molecular weight. If it is within this range, the dispersibility of the conductive agent is better, and the self stability of the synthesized waterborne polyurethane is better.

[0017] In the present invention, the hydrophilic compound comprises a hydrophilic group and 1 to 3 isocyanate reactive groups, the hydrophilic group of the hydrophilic compound comprises at least one of an ionic group, a potential ionic group, and a nonionic group; the isocyanate reactive group is preferably a hydroxyl group and / or an amino group; the ionic group is preferably a carboxylate (-COO - ) and / or sulfonate (-SO 3- ); the potential ionic group is preferably a carboxyl group and / or a sulfonic acid group; the nonionic group is preferably a polyoxyethylene ether.

[0018] The hydrophilic compound containing a nonionic group is preferably Ymer120 and / or a polyoxyethylene ether containing a hydroxyl group or an amino group, further preferably a monofunctional polyethoxy ether having a number average molecular weight of 200 to 8000 and an ethylene oxide number of 4 to 200, and more preferably a polyethylene glycol monomethyl ether having a number average molecular weight of 500 to 3000 and an ethylene oxide number of 12 to 75.

[0019] Preferably, the hydrophilic compound is selected from sodium ethylenediamineethanesulfonate, dihydroxymethylacetic acid, dihydroxymethylpropionic acid, dihydroxymethylbutyric acid, 2,6-diaminohexanoic acid, dihydroxysuccinic acid, N-(2-aminoethyl)-2-aminoethanesulfonic acid, N-(2-aminoethyl)-3-aminopropanesulfonic acid, N-(3-aminopropyl)-2-aminoethanesulfonic acid, N-(3-aminopropyl)-3-aminopropanesulfonic acid, and one or two of their salts.

[0020] If the hydrophilic compound contains potential ion groups, a neutralizer can be added to the composition before, during or after the hydrophilic compound component is added to the composition. The amount of the neutralizer added is such that part or all of the potential ion groups can be converted into ion groups; the neutralizer is preferably one or more of triethylamine, triethanolamine, dimethylethanolamine, 2-amino-2-methyl-1-propanol, N-methyldiethanolamine, dimethylcyclohexylamine, sodium carbonate, sodium bicarbonate, sodium hydroxide, potassium hydroxide, lithium hydroxide and calcium hydroxide. In general, the amount of the neutralizer added is such that the degree of neutralization is at least 50%, preferably at least 70%, and not more than 150% based on the total molar amount of the introduced acid groups. It is understood by those skilled in the art that in addition to the acid groups being neutralized to form ion groups, there are also free neutralizers in the system, and the degree of neutralization is particularly preferably 90-110%. Wherein, the degree of neutralization = the amount of the neutralizer added / the total amount of the introduced acid groups, in which the term "amount" refers to the molar amount. The pH value of the final waterborne polyurethane can also be used to determine the degree of neutralization. The pH value is 5 to 9, preferably controlled between pH 6 and 8. The stability of the overall adhesive and its application in the coating liquid composition are more compatible with the overall system.

[0021] In the present invention, the small molecule auxiliary agent is selected from a compound containing a phosphate group and containing one or more amino structures. The amino structure can be a primary monoamine or secondary monoamine of an aliphatic or alicyclic group. Specifically, the compound is selected from a phosphate compound containing one amino group, such as one or more of ethanolamine phosphate, 4-aminophenyl phosphate, biphenyl aminophosphoric acid ester, diphenyl aminophosphoric acid ester, and 2-amino-1,3-propanediol-3-phosphate; a phosphate compound containing more than one amino group, such as 1-(2-hydroxyethyl)-1-methylguanidine dihydrogen phosphate, aminophosphine (aminopropylaminoethyl thiophosphate), and aphidazole (S-[(4,6-diamino-1,3,5-triazine-2-yl)methyl]-O,O-dimethyl dithiophosphate). Preferably, one or more of ethanolamine phosphate, 4-aminophenyl phosphate, bis(4-aminophenyl) phosphate, diethyl N,N-bis(2-hydroxyethyl)aminomethylenephosphonate, and amifostine (aminopropylaminoethylthiophosphate) are used.

[0022] Optionally, the aqueous polyurethane binder further comprises a chain extender. There is no particular restriction on the content of the optional amino and / or hydroxyl compound. Specifically, for example, one or more of ethylamine, ethylenediamine, isophoronediamine, isopropylamine, butylamine or cyclohexylamine, hydroxyethylethylenediamine, ethanolamine, diethanolamine, N-methylethanolamine, diisopropanolamine and diethylenetriamine. The amount of the chain extender is 0.1 to 4%, preferably 2 to 3.5%.

[0023] On the other hand, the present invention also provides a method for preparing an aqueous polyurethane binder, the method comprising the following steps:

[0024] 1) reacting a polyisocyanate, a polyol, optionally a catalyst and optionally a portion of an organic solvent to obtain an isocyanate-terminated polyurethane prepolymer;

[0025] (2) reacting the polyurethane prepolymer obtained in step (1), a neutralizing agent and the remaining part, optionally an organic solvent,

[0026] The aqueous polyurethane binder is obtained by adding water for dispersion, adding a small molecule auxiliary agent and an optional chain extender for post-reaction, and finally removing the organic solvent.

[0027] Specifically, the reaction temperature of step (1) is 70-90°C, preferably, the reaction temperature is 75-85°C; the reaction of step (1) ends when the mass percentage of NCO groups in the reaction system reaches the theoretical value; the reaction temperature of step (2) is 30-60°C, preferably, the reaction temperature is 35-45°C; the reaction time of step (2) is 5-30min, preferably, the reaction time is 10-20min; the temperature of the post-reaction is 35-60°C, preferably, the temperature is controlled at 40-55°C; the time of the post-reaction is 5-30min, preferably, the time is 10-20min.

[0028] It should be noted that in the present invention, the type of the catalyst is not particularly limited, and an organic bismuth catalyst or an organic tin catalyst can be selected, preferably Bi@8108 or dimethyltin dineodecanoate from a leading American company, and more preferably dimethyltin dineodecanoate. The amount of the catalyst is 0.01 to 0.5 parts by mass, preferably 0.02 to 0.3 parts by mass

[0029] The organic solvent can be a solvent that is inert to isocyanate groups and can dissolve the generated urethane prepolymer. Examples of these solvents include dioxane, methyl ethyl ketone, dimethylformamide, tetrahydrofuran, N-methyl-2-pyrrolidone, toluene, propylene glycol monomethyl ether acetate, acetone, etc. The hydrophilic organic solvents used in the reaction are preferably removed at the end. The amount of organic solvent used is 0.5 to 4 times the total amount of other components, preferably 1 to 3 times. The portion added in step (1) accounts for 20 to 80%, preferably 30 to 70%.

[0030] Finally, the present invention provides an electrode coating liquid composition, comprising an active material, a conductive agent, a binder and the above-mentioned aqueous polyurethane binder.

[0031] The electrode coating liquid composition of the present invention is characterized by containing an active material, a conductive agent, a binder and the above-mentioned aqueous polyurethane binder. Relative to 100 parts by mass of the solid content of the electrode coating liquid composition, the mass proportions of each component are: 95-97 parts of active material, preferably 95.5-96.5 parts; 0.1-1.5 parts of conductive agent, preferably 0.2-1 parts; 2-4 parts of binder, preferably 2.5-3.5 parts, of which the aqueous polyurethane binder accounts for 0.5-4 parts, preferably 0.5-3.5 parts. Under the above-mentioned proportion range, an electrode for a storage device with high energy density, excellent coating processing performance, uniform dispersion of conductive agent, and low diaphragm resistance can be obtained, and then a storage device with both dynamic performance and cycle performance can be obtained, so it is preferred.

[0032] The active material described in the electrode coating liquid composition of the present invention is not particularly limited as long as it can insert / detach metal lithium or lithium ions, and known active materials can be used. For example, carbon materials such as natural graphite, artificial graphite, difficult graphitized carbon and easy graphitized carbon can be used. In addition, metal materials such as metal lithium, alloys, tin compounds, lithium transition metal nitrides, crystalline metal oxides, amorphous metal oxides, silicon compounds, conductive polymers, etc. can also be used. As specific examples, silicon oxygen negative poles and silicon carbon negative poles with porous carbon as the main body deposited silicon nanoparticles can be listed.

[0033] The conductive agent described in the electrode coating liquid composition of the present invention can be used as long as it is an electronic conductive material that does not adversely affect the battery performance. Usually, carbon black such as acetylene black and Ketjen black is used, but it can also be a conductive material such as natural graphite (scaly graphite, flaky graphite, earthy graphite, etc.), artificial graphite, carbon whisker, carbon fiber or metal (copper, nickel, aluminum, silver, gold, etc.) powder, metal fiber, conductive ceramic material, carbon nanotube slurry, etc. It is preferred that single-walled or multi-walled carbon nanotubes are combined with conductive carbon black.

[0034] The binder described in the electrode coating liquid composition of the present invention, in addition to the aqueous polyurethane binder provided by the present invention, can also be used in combination with a known binder, without particular limitation, and can list polymer compounds that are generally water-soluble and / or water-dispersible, as a specific example, can be used: polyvinylidene fluoride, polyvinylidene fluoride and hexafluoropropylene, perfluoromethyl vinyl ether and tetrafluoroethylene copolymers such as polyvinylidene fluoride copolymer resins, polytetrafluoroethylene, fluorine-based resins such as fluorine rubber, styrene-butadiene rubber, ethylene-propylene rubber, styrene-acrylonitrile copolymers and other polymers, polyurethane resins, acrylic resins, polyester resins, polyimide resins, polyamide resins and epoxy resins and other aqueous dispersions, and hydroxymethyl cellulose, carboxymethyl cellulose and its alkali metal salts, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose and other celluloses but not limited thereto. These additives can be used alone or in combination of two or more, or two or more resin composites can also be used.

[0035] It should be noted that the mixing method and sequence of the above-mentioned electrode materials of the electrode coating liquid composition of the present invention are not particularly limited, for example, the conductive aid, dispersant and binder composition can also be pre-mixed and used. As a mixing and dispersing device for mixing and dispersing the composition, there is no particular restriction, for example, a homogenizing disperser, a planetary mixer, a propeller mixer, a kneader, a homogenizer, an ultrasonic homogenizer, a colloid mill, a bead mill, a sand mill, a high-pressure homogenizer, etc. can be used.

[0036] The beneficial effects of the present invention are as follows: the polyolefin polyol has a low polarity alkyl chain, and the dispersion of the waterborne polyurethane adhesive to conductive carbon black, carbon nanotubes and other conductive agents can be improved by regulating a specific ratio with a hydrophilic compound, and the adhesion to the metal foil can be improved by the phosphate group in the small molecule additive, and the obtained waterborne polyurethane adhesive can have a flexible and tough structural property by matching the isocyanate with the small molecule additive, so as to meet the long-term application requirements of the adhesive in the battery core. The adhesive is applied to the electrode coating liquid composition, and the dispersion of the conductive agent can be characterized by slurry dispersibility, electron microscopy, etc., and the dispersion is more uniform, and the membrane resistance is lower, and the obtained storage device has excellent dynamic performance, and has the characteristics of better bonding stability, no material loss during disassembly, good cycle performance, and low rebound expansion during the long-term circulation of the storage device. DETAILED DESCRIPTION

[0037] The embodiments of the present invention are further described below in conjunction with examples, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the rights claimed by the present invention.

[0038] Raw materials and sources:

[0039] Some of the raw material information involved in the specific implementation of the present invention is as follows:

[0040] Hexamethylene diisocyanate (HDI): industrial grade, Wanhua Chemical Group Co., Ltd.

[0041] Dicyclohexylmethane diisocyanate (HMDI): industrial grade, Wanhua Chemical Group Co., Ltd.

[0042] Isophorone diisocyanate (IPDI): industrial grade, Wanhua Chemical Group Co., Ltd.

[0043] Methylene diphenyl diisocyanate (MDI): industrial grade, Wanhua Chemical Group Co., Ltd.

[0044] Polybutadiene polyol (manufactured by CREY VALLE, LBH-P3000, Mn=3000 g / mol)

[0045] Polybutadiene polyol (manufactured by Crey Valley Co., Ltd., Poly-bd R45V, Mn = 2000 g / mol)

[0046] Hydrogenated polybutadiene polyol (Japan Soda GI-3000, Mn = 3000 g / mol)

[0047] Hydrogenated polybutadiene polyol (manufactured by Crey Valley, HLBH-P2000, Mn=2000 g / mol)

[0048] Ethanolamine phosphate: purity 99.0%, Shanghai Aladdin Biochemical Technology Co., Ltd.

[0049] 4-Aminophenyl phosphate: purity ≥97%, Shanghai Huicheng Biotechnology Co., Ltd.

[0050] Bis(4-aminophenyl)phosphate: purity 98.0%, Shanghai Hansi Chemical Co., Ltd.

[0051] N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester: purity 99.0%, Hubei Hanwei Chemical Co., Ltd.

[0052] Catalyst: dimethyltin diceneodecanoate, reagent grade, Bidex Pharmaceuticals;

[0053] Acetone: industrial grade, Shandong Hongyang Chemical Co., Ltd.;

[0054] Methyl ethyl ketone: industrial grade, Zibo Qixiang Tengda Chemical Co., Ltd.;

[0055] Dimethylolpropionic acid (DMPA): technical grade, Perstorp Chemical Company;

[0056] Triethylamine: analytical grade, Sinopharm Chemical Reagent Co., Ltd.;

[0057] Ethylenediamine: analytical grade, Sinopharm Chemical Reagent Co., Ltd.;

[0058] Diethylenetriamine: analytical grade, Sinopharm Chemical Reagent Co., Ltd.;

[0059] Other raw materials are conventional products unless otherwise specified and can be purchased from the market.

[0060] Synthesis Example 1: Synthesis of Waterborne Polyurethane Binder I

[0061] 67.46 parts by mass of polybutadiene polyol LBH-P3000, 4.2 parts by mass of dimethylol propionic acid (active hydrogen number 2), 24.5 parts by mass of HDI (hexamethylene diisocyanate), 100 parts by mass of acetone, and 0.2 parts by mass of dimethyltin dineodecanoate were placed in a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet. The mixture was stirred at 80°C until NCO reached the theoretical value. The prepolymer was dissolved in 100 parts by mass of acetone and cooled to 50°C. 30 parts by mass of an aqueous solution containing 2 parts by mass of lithium hydroxide, 3.42 parts by mass of isophorone diamine, and 0.4 parts of ethanolamine phosphate (SIGMA) were added to the acetone solution containing the prepolymer, respectively, and stirred for 20 minutes while stirring vigorously at a speed of 300 r / min, and 1.5 parts by mass of lithium hydroxide was added, neutralized, and then the mixture was dispersed by adding 200 parts by mass of 1 water. After the acetone is separated by distillation, a polyurethane aqueous dispersion I having a non-volatile content of about 25% is obtained, which has good mechanical strength.

[0062] Synthesis Example 2: Synthesis of Waterborne Polyurethane Binder II

[0063] 50.9 parts by mass of hydrogenated polybutadiene polyol GI-3000, 6 parts by mass of dimethylol propionic acid (active hydrogen number 2), 39.6 parts by mass of HMDI (4,4-diisocyanate dicyclohexylmethane), 100 parts by mass of acetone, and 0.2 parts by mass of dimethyltin dineodecanoate were placed in a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet. The mixture was stirred at 80°C until NCO reached the theoretical value. The prepolymer was dissolved in 100 parts by mass of methyl ethyl ketone and cooled to 40°C, and 4.5 parts by mass of triethylamine was added for neutralization, and then 300 parts by mass of water was slowly added, and emulsified and dispersed using a disperser. Next, an aqueous solution of 0.5 parts by mass of hydroxyethylethylenediamine and 3 parts by mass of 4-aminophenyl phosphate (Shanghai Tongtian Biotechnology Co., Ltd.) diluted with 100 parts by mass of water was added, and a chain extension reaction was carried out for 1 hour. The solution was decompressed and heated at 50°C to remove the solvent, thereby obtaining a polyurethane aqueous dispersion II having a nonvolatile content of about 25%.

[0064] Synthesis Example 3: Synthesis of Waterborne Polyurethane Binder III

[0065] 55.4 parts by mass of polybutadiene polyol Poly bd R45V, 3.2 parts by mass of dimethylol propionic acid (active hydrogen number 2), 25 parts by mass of IPDI (isophorone diisocyanate), 11 parts by mass of MDI (diphenylmethane diisocyanate, 2,4-content 47%), 100 parts by mass of methyl ethyl ketone, and 0.2 parts by mass of dimethyltin dineodecanoate were placed in a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet. The mixture was stirred at 80°C until NCO reached the theoretical value. The prepolymer was dissolved in 100 parts by mass of methyl ethyl ketone and cooled to 40°C. After neutralization by adding 3 parts by mass of sodium hydroxide, 300 parts by mass of water was slowly added and emulsified and dispersed using a disperser. Then, an aqueous solution prepared by diluting 1.2 parts by mass of bis(4-aminophenyl)phosphate and 2.2 parts by mass of diethylenetriamine with 100 parts by mass of water was added to carry out a chain extension reaction for 1 hour. The solution was decompressed and heated at 60°C to remove the solvent, thereby obtaining a polyurethane aqueous dispersion III having a nonvolatile content of about 25%.

[0066] Synthesis Example 4: Synthesis of Waterborne Polyurethane Binder IV

[0067] 60.5 parts by mass of hydrogenated polybutadiene polyol (manufactured by Idemitsu Kosan Co., Ltd., PolybdR-45HT, Mn=2000), 32.85 parts by mass of HMDI (4,4-diisocyanate dicyclohexylmethane), 200 parts by mass of acetone, and 0.2 parts by mass of dimethyltin dineodecanoate were placed in a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet. The mixture was stirred at 80°C until NCO reached a theoretical value. The prepolymer was dissolved in 100 parts by mass of acetone and cooled to 50°C, and 35 parts by mass of an aqueous solution in which 3 parts by mass of sodium N-(2-aminoethyl)-2-aminoethanesulfonate, 1.15 parts by mass of N,N-dimethyldipropylenetriamine, and 2.5 parts by mass of amifostine were dissolved was added to the acetone solution in which the prepolymer was dissolved while vigorously stirring for 20 minutes, and then the mixture was dispersed by adding 200 parts by mass of water. The solution was decompressed and heated at 60°C to remove the solvent, thereby obtaining a polyurethane aqueous dispersion IV having a nonvolatile content of about 25%.

[0068] Comparative Synthesis Example 5: Synthesis of Non-Polyolefin Waterborne Polyurethane Binder V

[0069] 50.9 parts by mass of poly(1,4-butylene adipate diol) (Wanhua Chemical, PBA-2000, Mn=2000), 6 parts by mass of dimethylol propionic acid (active hydrogen number 2), 39.6 parts by mass of HMDI (4,4-diisocyanate dicyclohexylmethane), and 100 parts by mass of acetone were placed in a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet. The mixture was stirred at 80°C until NCO reached the theoretical value. The prepolymer was dissolved in 100 parts by mass of methyl ethyl ketone and cooled to 40°C, 4.5 parts by mass of triethylamine was added, and after neutralization, 300 parts by mass of water was slowly added, and emulsified and dispersed using a disperser. Next, an aqueous solution of 0.5 parts by mass of hydroxyethylethylenediamine and 3 parts by mass of 4-aminophenyl phosphate (Shanghai Tongtian Biotechnology Co., Ltd.) diluted with 100 parts by mass of water was added, and a chain extension reaction was carried out for 1 hour. The solution was decompressed and heated at 50°C to remove the solvent, thereby obtaining a polyurethane aqueous dispersion V having a nonvolatile content of about 25%.

[0070] Comparative Synthesis Example 6: Synthesis of Waterborne Polyurethane Binder VI

[0071] 67.46 parts by mass of polybutadiene polyol (KRASOL LBH-P3000 manufactured by CREY VALLEY, Mn=3000), 4.2 parts by mass of dimethylol propionic acid (number of active hydrogens: 2), 24.5 parts by mass of HDI (hexamethylene diisocyanate), and 100 parts by mass of acetone were placed in a 1L four-necked round-bottom flask equipped with a nitrogen inlet and outlet. The mixture was stirred at 80°C until NCO reached a theoretical value. The prepolymer was dissolved in 100 parts by mass of acetone and cooled to 50°C. 30 parts by mass of an aqueous solution in which 2 parts by mass of lithium hydroxide and 3.82 parts by mass of isophorone diamine were respectively added to the acetone solution in which the prepolymer was dissolved, and stirred for 20 minutes while vigorously stirring at a rotation speed of 300 r / min, and 1.5 parts by mass of lithium hydroxide was added to neutralize the mixture, and then 200 parts by mass of water were added to disperse the mixture. After the acetone was separated off by distillation, an aqueous polyurethane dispersion VI having a nonvolatile content of about 25% was obtained.

[0072] The evaluation method and evaluation criteria of waterborne polyurethane adhesives are as follows:

[0073] Preparation of dry film: Pour the waterborne polyurethane adhesives I to VI obtained in the above-mentioned synthesis examples 1-6 into a polytetrafluoroethylene plate with grooves, and dry them in an oven at 60° C. for 48 hours to prepare an adhesive film with a thickness of about 100 μm.

[0074] Strength and elongation test: Cut the flat part of the dry film surface into dumbbell shape, and use the American Tesla machine, MTS Model E43, to test at a pulling speed of 10mm / min.

[0075] Electrolyte swelling rate test: Take another 3cm×3cm film and immerse it in an electrolyte with a solvent volume ratio of 1:1:1 of diethyl carbonate, ethylene carbonate and propylene carbonate and a lithium salt of 1M LiPF6. Seal it and heat store it at 60℃ for 7 days. After wiping off the surface electrolyte, measure the percentage increase of the film mass (swelling rate of absorbing electrolyte).

[0076] Conductive agent compatibility test: The aqueous polyurethane binder I to VI obtained in the above-mentioned synthesis examples 1-6 were diluted and dispersed with commercially available single-walled carbon tube slurry using a disperser for 2 hours. The viscosity of the 4% solid slurry was tested at 25°C after 48 hours to characterize the compatibility of the aqueous polyurethane binder and the conductive agent. The lower the viscosity, the better the compatibility.

[0077] The test results of waterborne polyurethane binders I to VI according to the above test method are shown in Table 1:

[0078] Table 1

[0079] StrengthMpa Elongation % Swelling rate % Compatibility viscosity cps Synthesis example 1 7.8 250 45 1580 Synthesis example 2 26.2 46 28 2340 Synthesis example 3 24.5 68 38 1800 Synthesis example 4 18.4 115 52 2240 Comparative Synthesis Example 5 29.2 12 280 >5000 Comparative Synthesis Example 6 7.2 242 42 1780

[0080] It can be seen from Table 1 that the waterborne polyurethane binders obtained by Synthesis Examples 1-4 all have lower swelling ratios and high conductive agent compatibility.

[0081] Example 1: Graphite electrode coating liquid composition 1

[0082] An electrode coating liquid composition is composed of the following components in parts by solid weight:

[0083]

[0084] Example 2: Graphite electrode coating liquid composition 2

[0085] An electrode coating liquid composition is composed of the following components in parts by solid weight:

[0086]

[0087] Example 3: 5% Silicon System Electrode Coating Liquid Composition 3

[0088] An electrode coating liquid composition is composed of the following components in parts by weight:

[0089]

[0090]

[0091] Example 4: 5% silicon system electrode coating liquid composition 4 An electrode coating liquid composition is composed of the following components in parts by weight:

[0092] Example 5: 15% Silicon System Electrode Coating Liquid Composition 5 An electrode coating liquid composition is composed of the following components in parts by weight:

[0093] Example 6: 15% Silicon System Electrode Coating Liquid Composition 6 A coating liquid composition for an electrode is composed of the following components in parts by weight:

[0094] Example 7: Graphite electrode coating liquid composition 7

[0095] An electrode coating liquid composition is composed of the following components in parts by weight:

[0096]

[0097] Comparative Example 1: Graphite electrode coating liquid composition 8

[0098] An electrode coating liquid composition is composed of the following components in parts by weight:

[0099] Comparative Example 2: Silicon-based electrode coating liquid composition 9

[0100] An electrode coating liquid composition is composed of the following components in parts by weight:

[0101] Comparative Example 3: Silicon system electrode coating liquid composition 10 A coating liquid composition for an electrode is composed of the following components in parts by weight:

[0102] Comparative Example 4: Silicon System Electrode Coating Liquid Composition 11 A coating liquid composition for an electrode is composed of the following components in parts by weight:

[0103]

[0104] Comparative Example 5: Silicon-based electrode coating liquid composition 12

[0105] An electrode coating liquid composition is composed of the following components in parts by weight:

[0106]

[0107] The evaluation method and evaluation criteria of the coating liquid composition and the negative electrode sheet are as follows:

[0108] Preparation method of coating liquid composition and negative electrode sheet: The electrode coating liquid composition in the above embodiment and comparative example is stirred by a double planetary agitator for the same slurry process time to prepare a negative electrode slurry with a solid content of 40%. After vacuum defoaming, 1L of slurry is taken out for evaluation test. The remaining negative electrode slurry is then coated on 8μm lithium battery copper foil by a coating machine, dried at 85°C, and then rolled to obtain a negative electrode with a surface density of 20mg / cm on both sides. 2 The obtained negative electrodes are respectively mixed with the corresponding electrode coating liquid compositions to form negative electrodes 1-12.

[0109] 1. Slurry viscosity: Use Brookfield-LV rotary viscometer, No. 63 rotor, 12rpm / min to test the viscosity at 25℃;

[0110] 2. Slurry fineness: Use a 0-100μm scraper applicator to read the value after scraping. The lower the value, the better the dispersion.

[0111] 3. Slurry filtration time. Take 500 ml of the dispersed slurry and record the time required for 150-mesh filter to filter out 300 ml of slurry. The shorter the filtration time, the better the dispersion.

[0112] 4. Conductive agent dispersion uniformity: Randomly select points on the negative electrode sheet and observe the conductive agent distribution uniformity under 50,000 times and 500,000 times through SEM scanning electron microscope, and evaluate it on a scale of 1-5, 1 point: a large number of agglomerates or particles, 5 points: uniform dispersion.

[0113] 5. Battery performance evaluation mainly evaluates the battery's cycle charge and discharge performance and the battery's DC internal resistance. After the cycle, the battery cell is disassembled to observe the material loss of the negative electrode.

[0114] The negative electrode sheet is used to prepare the evaluation battery, and the positive electrode of the battery is LiNi 0.5 Co 0.2 Mn 0.3 O2 (Hunan Yuneng YN-5), the electrolyte used was EC:EMC:DEC=3:5:2, 1 mol / L LiPF6, and a button cell for evaluation was prepared.

[0115] The DC internal resistance performance of the battery is based on the DC internal resistance value of the battery at -10°C after the initial charge and discharge (50% SOC, 0.36C, 30s).

[0116] The cyclic charge and discharge performance is as follows: CC (constant current) charging is performed at a current density equivalent to 0.5C to 4.2V, and then switching to CV (constant voltage) charging at 4.2V. After charging for 1.5 hours, CC discharge is performed at a current density equivalent to 0.5C to 2.7V. This cycle is repeated 300 times at 20°C. The ratio of the 1C discharge capacity after 300 cycles to the initial 0.5C discharge capacity is taken as the 0.5C charge and discharge cycle retention rate. The higher the retention rate, the better the battery cycle stability.

[0117] The negative electrode was disassembled after 300 cycles and scored according to the shedding of surfactant. 1 point means that the entire electrode fell off the foil, and 10 points means that the electrode structure was intact without any powder particles falling off.

[0118] Table 2

[0119]

[0120] As can be seen from Table 2, through Example 1 and Comparative Example 1, Example 4 and Comparative Example 2, and Example 6 and Comparative Example 3, it can be concluded that in the conductive agent matching system with different degrees of difficulty in dispersion, after adding the aqueous polyurethane dispersant of different synthesis examples, the slurry viscosity is lower, the conductive agent dispersion performance is better, and the electrochemical cycle and internal resistance are both better.

[0121] In addition, by comparing Example 4 with Example 5, it can be seen that when the amount of the waterborne polyurethane binder is increased, the dispersion of the conductive agent will be better, and the corresponding electrochemical cycle and internal resistance performance will be improved.

[0122] In addition, it can be seen from Comparative Example 4 and Example 6 that the water-based polyurethane whose polyol is a non-polyolefin system has poor dispersibility. Although the introduction of phosphate groups slightly improves the disassembly and dropout situation, the overall electrochemical performance is poor.

[0123] It can be seen from Comparative Example 5 and Example 6 that the waterborne polyurethane battery cells containing phosphate groups generally perform better in terms of material shedding after disassembly than the waterborne polyurethane battery cells without phosphate groups, and have better adhesion.

[0124] Finally, it should be noted that the above embodiments are only used to describe the preferred implementation methods of the present invention, rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that various modifications and improvements made by modifying or equivalently replacing the technical solution of the present invention should fall within the protection scope determined by the claims of the present invention.

Claims

1. A water-based polyurethane binder for a battery, which is prepared by polymerization reaction of raw materials including polyisocyanate, polyol, hydrophilic compound, small molecule additive and the like. In parts by weight, the mass ratio of the polyisocyanate, polyol, hydrophilic compound and small molecule additive is 15-50: 40-75: 2-10: 0.05-5, and the preferred mass ratio is 20-40: 50-70: 3-8: 0.1-4.

2. The aqueous polyurethane binder for batteries according to claim 1, characterized in that The polyisocyanate is selected from one or more of aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, and aromatic aliphatic polyisocyanates; and / or the polyol is an olefin polyol containing 1.5 or more active hydrogen atoms; for example, polyols such as polybutadiene polyol, polyisoprene polyol, polychloroprene polyol, or hydrogenated polyols thereof, and polyols obtained by copolymerizing olefin compounds such as styrene, ethylene, vinyl acetate, and acrylate in polybutadiene polyol, or hydrogenated polyols thereof; polybutadiene polyol, polyisoprene polyol, hydrogenated polybutadiene polyol, and hydrogenated polyisoprene polyol are particularly preferred.

3. The aqueous polyurethane binder for batteries according to claim 1 or 2, characterized in that: The hydrophilic compound comprises a hydrophilic group and 1 to 3 isocyanate-reactive groups, and the hydrophilic group of the hydrophilic compound comprises at least one of an ionic group, a potential ionic group, and a non-ionic group; the isocyanate-reactive group is preferably a hydroxyl group and / or an amino group; preferably, the ionic group is preferably a carboxylate and / or a sulfonate group; the potential ionic group is preferably a carboxyl group and / or a sulfonic acid group; the non-ionic group is preferably a polyoxyethylene ether; further preferably, the hydrophilic compound is selected from sodium ethylenediamineethanesulfonate, dihydroxymethylacetic acid, dihydroxymethylpropionic acid, dihydroxymethylbutyric acid, 2,6-diaminohexanoic acid, dihydroxysuccinic acid, N-(2-aminoethyl)-2-aminoethanesulfonic acid, N-(2-aminoethyl)-3-aminopropanesulfonic acid, N-(3-aminopropyl)-2-aminoethanesulfonic acid, N-(3-aminopropyl)-3-aminopropanesulfonic acid, and one or two of their salts.

4. The aqueous polyurethane binder for batteries according to any one of claims 1 to 3, characterized in that: The small molecule auxiliary agent is selected from a compound containing a phosphate group and containing more than one amino structure, such as ethanolamine phosphate, 4-aminophenyl phosphate, biphenyl aminophosphorate, diphenyl aminophosphorate, 2-amino-1,3-propanediol-3-phosphate, 1-(2-hydroxyethyl)-1-methylguanidine dihydrogen phosphate, amifostine (aminopropylaminoethylthiophosphate), aphidoxine (S-[(4,6-diamino-1,3,5-triazine-2-yl)methyl]-O,O-dimethyldithiophosphate), ethanolamine phosphate, 4-aminophenyl phosphoric acid, bis(4-aminophenyl) phosphate, N,N-bis(2-hydroxyethyl)aminomethylenephosphonic acid diethyl ester, and amifostine (aminopropylaminoethylthiophosphate).

5. The method for preparing the aqueous polyurethane binder for batteries according to any one of claims 1 to 4, comprising the following steps: 1) reacting a polyisocyanate, a polyol, optionally a catalyst and optionally an organic solvent to obtain an isocyanate-terminated polyurethane prepolymer; (2) reacting the polyurethane prepolymer obtained in step (1), a neutralizing agent and an optional organic solvent, adding water for dispersion, then adding a small molecule auxiliary agent and an optional chain extender for post-reaction, and finally removing the organic solvent to obtain the waterborne polyurethane binder.

6. The preparation method according to claim 5, characterized in that: The reaction temperature of step (1) is 70-90°C, preferably, the reaction temperature is 75-85°C; and / or, the reaction of step (1) ends when the mass percentage of NCO groups in the reaction system reaches the theoretical value; and / or, the reaction temperature of step (2) is 30-60°C, preferably, the reaction temperature is 35-45°C; and / or, the reaction time of step (2) is 5-30min, preferably, the reaction time is 10-20min; and / or, the temperature of the post-reaction is 35-60°C, preferably, the temperature is controlled at 40-55°C; the time of the post-reaction is 5-30min, preferably, the time is 10-20min.

7. A coating liquid composition for an electrode, comprising an active material, a conductive agent, a binder, and the aqueous polyurethane binder for a battery as claimed in any one of claims 1 to 4 or the aqueous polyurethane binder for a battery prepared by the preparation method as claimed in any one of claims 5 to 6.

8. The electrode coating liquid composition according to claim 7, characterized in that Relative to 100 parts by mass of the solid content of the electrode coating liquid composition, the mass proportions of each component are: 95-97 parts of active material, preferably 95.5-96.5 parts; 0.1-1.5 parts of conductive agent, preferably 0.2-1 parts; 2-4 parts of binder, preferably 2.5-3.5 parts, of which water-based polyurethane binder accounts for 0.5-4 parts, preferably 0.5-3.5 parts.

9. The electrode coating liquid composition according to claim 7 or 8, characterized in that The active material is selected from one or more of natural graphite, artificial graphite, difficult-graphitizing carbon and easy-graphitizing carbon or metallic lithium, alloys, tin compounds, lithium transition metal nitrides, crystalline metal oxides, amorphous metal oxides, silicon compounds, and conductive polymers, preferably silicon-oxygen negative electrodes and silicon-carbon negative electrodes; and / or, the conductive agent is selected from one or more of acetylene black, Ketjen black, natural graphite (scaly graphite, flaky graphite, earthy graphite, etc.), artificial graphite, carbon whiskers, carbon fibers, or metal (copper, nickel, aluminum, silver, gold, etc.) powders, metal fibers, conductive ceramic materials, and carbon nanotube slurries; preferably single-walled or multi-walled carbon nanotubes are combined with conductive carbon black.

10. The electrode coating liquid composition according to any one of claims 7 to 9, characterized in that: The binder also includes one or more of polyvinylidene fluoride, copolymers of polyvinylidene fluoride and hexafluoropropylene, perfluoromethyl vinyl ether and tetrafluoroethylene, polytetrafluoroethylene, fluororubber, styrene-butadiene rubber, ethylene-propylene rubber, styrene-acrylonitrile copolymer, polyurethane resin, acrylic resin, polyester resin, polyimide resin, polyamide resin and epoxy resin, hydroxymethyl cellulose, carboxymethyl cellulose and its alkali metal salt, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl methyl cellulose.

Citation Information

Patent Citations

  • Methods for preparing carbon nanotubes and carbon nanotube dispersion compositions

    CN106413949B

  • Binder composition for electrode, coating composition for electrode, electrode for power storage device, and power storage device

    CN113711383A